Employee productivity spillovers generated by incentive schemes - Gerhardus van Zyl; Mpho D. Magau (SA Journal of Human Resource Management, 2024)
Orientation: The introduction of various incentive schemes in the South African workplace creates incentive-induced employee productivity spillovers but could differ between industries and geographic areas.